1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Proving a Trigonometric Identity

  1. Jun 29, 2008 #1
    Im supposed to verify that (1-sinx)/(1+sinx) = (secx-tanx)^2

    RHS = (secx-tanx)^2 = (1/cosx - sinx/cosx)^2 = [(1-sinx) / cosx]^2

    = [(1-sinx)(1-sinx)]/cosx^2 = (1-2sinx+sinx^2)/(1-sinx^2)

    From here, I'm feeling pretty confused. I'm not even sure if all my values are correct.
  2. jcsd
  3. Jun 29, 2008 #2
    From there it's important to recognize that (1-a^2)=(1+a)(1-a) and then (1-2a-a^2)=(1-a)^2=(1-a)(1-a). Then it's just a matter of removing the common term.


    Last edited by a moderator: Apr 23, 2017 at 1:52 PM
  4. Jun 29, 2008 #3

    starting from: [(1-sinx) / cosx]^2 = [(1-sinx)(1-sinx)]/cosx^2

    using pythagorean identity

    [(1-sinx)/(1-sinx)]/(1-sinx^2) = [(1-sinx)/(1-sinx)]/[(1-sinx)(1+sinx)] = (1-sinx)/(1+sinx) = RHS

Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Similar Discussions: Proving a Trigonometric Identity